2021
DOI: 10.1161/hypertensionaha.121.17298
|View full text |Cite
|
Sign up to set email alerts
|

Epididymal Fat-Derived Sympathoexcitatory Signals Exacerbate Neurogenic Hypertension in Obese Male Mice Exposed to Early Life Stress

Abstract: Previously, we have shown that male mice exposed to maternal separation and early weaning (MSEW)—a mouse model of early life stress—display increased mean arterial pressure compared with controls when fed a high-fat diet. As the stimulation of sensory nerves from fat has been shown to trigger the adipose afferent reflex, we tested whether MSEW male mice show obesity-associated hypertension via the hyperactivation of this sympathoexcitatory mechanism. After 16 weeks on high-fat diet, MSEW mice displayed increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 99 publications
0
12
0
Order By: Relevance
“…An increase in cFos, a marker of neuronal activation, after activation of adipose afferents was documented in different nuclei, including the rostral ventrolateral medulla, organum vasculosum of the lamina terminalis, and paraventricular nucleus of the hypothalamus (PVN). 88,90 Adipose afferent reflexinduced increase in discharge activity of individual PVN neurons was confirmed using direct recording. 92 Moreover, chemically mediated lesioning of the PVN neurons with kainic acid abolished the adipose afferent reflex induced by injection of capsaicin into the inguinal fat depot.…”
Section: Cardiovascular Effects Of the Adipose Afferent Reflexmentioning
confidence: 81%
See 2 more Smart Citations
“…An increase in cFos, a marker of neuronal activation, after activation of adipose afferents was documented in different nuclei, including the rostral ventrolateral medulla, organum vasculosum of the lamina terminalis, and paraventricular nucleus of the hypothalamus (PVN). 88,90 Adipose afferent reflexinduced increase in discharge activity of individual PVN neurons was confirmed using direct recording. 92 Moreover, chemically mediated lesioning of the PVN neurons with kainic acid abolished the adipose afferent reflex induced by injection of capsaicin into the inguinal fat depot.…”
Section: Cardiovascular Effects Of the Adipose Afferent Reflexmentioning
confidence: 81%
“…Moreover, in these mice, selective denervation of afferents emanating from the epididymal fat reduced blood pressure and attenuated the sympathetic index. Denervation of the kidneys also blunted the chronic blood pressure elevation and the acute capsaicin-induced pressor response in diet-obese mice exposed to early life stress, 90 implicating the renal nerves in mediating the changes observed in these mice.…”
Section: Afferent Nerves and Cardiometabolic Crosstalkmentioning
confidence: 83%
See 1 more Smart Citation
“…Male and female mice that have undergone early-life stress develop hypertension after placement on a high-fat diet. However, they appear to develop hypertension differently, with male mice displaying increased sympathetic activation, and female mice showing greater adiposity and metabolic compromise [ 52 ]. The higher PHQ-2 and PHQ-9 scores in our male participants with T2D might reflect increased stress and may be associated with sympathetic activation.…”
Section: Discussionmentioning
confidence: 99%
“…Dalmasso et al recently demonstrated that the stimulation of afferent sensory nerves from visceral white adipose tissue could increase blood pressure in normal mice [ 11 ]. They further showed that afferent signals from visceral white adipose tissue contributed to sympathetic activation and hypertension in male mice exposed to early life stress when fed an obesogenic diet [ 12 ]. This enhanced sympathetic outflow was most likely mediated by increased afferent signals from epididymal white adipose tissue projecting to brain areas with a pivotal role in developing neurogenic hypertension, such as the hypothalamic paraventricular nucleus (PVN) and rostral ventrolateral medulla (RVLM).…”
Section: Introductionmentioning
confidence: 99%